Safety and immunogenicity of a new formulation of a pentavalent DTwP-HepB-Hib vaccine in healthy Indian infants-A randomized study. - Naveena Aloysia D'Cor; Prashanth Siddaiah; Satyajit Mohapatra; Sangappa Malappa Dhaded; Padmavathi I V; Sonali Kar; Tripathi V N; Prasad Muley; Jugesh Chhatwal; Badri Narayan Patnaik; Emmanuel Vidor; Annick Moureau; et al. (PLoS ONE, 2023)
Background Pentavalent vaccines (DTP-HepB-Hib) have been introduced in many countries in their routine public immunization programmes to protect against diphtheria (D), tetanus (T), pertussis (P), hepatitis B (Hep B) and Hemophilus influenzae type b (Hib) diseases. This study compared the safety and immunogenicity of a new formulation of a whole-cell Bordetella pertussis (wP) based pentavalent vaccine (DTwP-HepB-Hib). The new formulation was developed using well-characterized hepatitis B and pertussis whole cell vaccine components. Methods This was a phase III, observer-blind, randomized, non-inferiority, multi-center study conducted in India among 460 infants who were followed up for safety and immunogenicity for 28 days after administration of three doses of either investigational or licensed comparator formulations at 6-8, 10-12 and 14-16 weeks of age. Results The investigational formulation of DTwP-HepB-Hib vaccine was non-inferior to the licensed formulation in terms of hepatitis B seroprotection rate (% of subjects with HepB antibodies ≥10mIU/mL were 99.1% versus 99.0%, respectively, corresponding to a difference of 0.1% (95% CI, -2.47 to 2.68)) and pertussis immune responses (adjusted geometric mean concentrations of antibodies for anti-PT were 76.7 EU/mL versus 63.3 EU/mL, with a ratio of aGMTs of 1.21 (95% CI, 0.89-1.64), and for anti-FIM were 1079 EU/mL versus 1129 EU/mL, with a ratio of aGMTs of 0.95 (95% CI, 0.73-1.24), respectively). The immune responses to other valences (D, T, and Hib) in the two formulations were also similar. The safety profile of both formulations was found to be similar and were well tolerated. Conclusions The investigational DTwP-HepB-Hib vaccine formulation was immunogenic and well-tolerated when administered as three dose primary series in infants. Clinical trial registration Clinical Trials Registry India number: CTRI/2018/12/016692.